ÉTUDE DE L’IMPACT DES VARIATIONS PLUVIOMÉTRIQUES SUR LES FLUCTUATIONS PIÉZOMÉTRIQUES DES NAPPES PHRÉATIQUES SUPERFICIELLES EN ZONE SEMI-ARIDE (CAS DE LA PLAINE DE SAÏSS, NORD DU MAROC) - Abdelhamid, El ibrahimi; Baali, Abdennasser; Amine, Couscous; Touria, El kamel (European Scientific Journal, ESJ, 2015)
Looking at their climate regime, the plain of Saïss is part of semi-arid areas of Morocco which are subject to the influences of the rapid increase in population and their needs for water and the effects of climate change increasingly worrisome. This situation represents a strong constraint for the reserves of sensitive groundwater in the plain. The aim of this contribution is to highlight the existence of climate variability, manifested primarily by variability in the amount of rainfall and irregularities in the plain studied and highlight its impact on food of groundwater reserves, in the surface water table. To do this, various data (rainfall and piezometry) and methods (The Standardized Precipitation Index (SPI), homogeneity test and cumulative rainfall, Statistics Buishand, test PETTIT, Bayesian method LEE and HEGHINIAN and procedure Hubert segmentation) were used. In the light of the results obtained, a climate variability characterized by alternating wet, normal and dry phases were identified in the study area. The indices and statistical methods indicate the existence of a break in 2008-2009 manifested by changes in rainfall patterns. The symptoms of this climatic variability from affecting groundwater resources. A significant decrease in the static level of the surface water table appears in the piezometers witnesses to a low level in 2002/2003, indicating an anomaly in the sampling report / recharging the superficial aquifer